PENGELOLAAN AKUN INSTAGRAM @alifakids DALAM MEMPERTAHANKAN BRAND AWARENESS TK ALIFA KIDS - Sartika, Elsi Olivia (Fakultas Dharma Duta, 2025)
In this era of digitalization, it is important for a company/institution to improve its branding. Alifa Kids Kindergarten is a good example of their strategy to improve their branding. By having Public Relations in Alifa Kids Kindergarten, this strategy can be made easier. In building brand awareness, TK Alifa Kids focuses on social media, especially on Instagram. TK Alifa Kids is very serious and detailed in developing the TK Alifa Kids Instagram account (@alifakids). They pay attention to the posting schedule, the essence of neatness of stories, feeds & reels, advertising Instagram stories, and contacting the audience by distributing promotional broadcasts via direct messages. With the various strategies that Alifa Kids Kindergarten implements, engagement can increase, as a result the reach of the target audience expands. This is very effective in increasing brand awareness of Alifa Kids Kindergarten.